Philosophical foundations of education - Ozmon, Howard (Pearson/Merrill Prentice Hall, 2008)
[This text] provides balanced treatment of all the major schools of thought about education. The authors address how philosophical ideas about education developed over time--arranging their coverage in chronological order--and pay close attention to historical context, while emphasizing each philosophy's continuing relevance to education today. For each philosophy, they show its application in aims, curriculum, methods, and teaching. Additionally, they critically assess each philosophy, and examine how numerous other scholars view it. [It] offers a greater emphasis on women and minorities such as Montessori, De Beauvoir, Greene, DeBois, King, and West. -http://www.booksintprin.com